Cloud-Based ERP Implementation Challenges in Small Industries - Handoko, Yusuf (Omnia Tempus, 2024)
This study investigates the multifaceted challenges faced by small industries in implementing cloud-based Enterprise Resource Planning (ERP) systems, aiming to provide a comprehensive understanding of the technical, organizational, and human-centric barriers that hinder adoption. Employing a qualitative research design, the study adopts an interpretivist approach through a systematic literature review of 45 peer-reviewed articles published between 2010 and 2024. Data were analyzed thematically using ATLAS.ti, enabling the identification of key implementation challenges and contextual factors shaping ERP adoption in resource-constrained industrial environments. The findings reveal three primary categories of obstacles: infrastructure and technological deficiencies, organizational unreadiness coupled with resistance to change, and significant human resource and knowledge gaps. Specifically, the study finds that inadequate digital infrastructure, cultural inertia, and the absence of sustained training programs frequently result in project delays, underutilized systems, and operational inefficiencies. Moreover, cloud-based ERP systems' success depends heavily on contextual alignment with the firm’s internal capabilities, strategic planning processes, and commitment to long-term digital transformation. These insights contribute to existing theoretical models such as the Technology-Organization-Environment (TOE) framework by highlighting the role of sustainability-oriented digital strategies and adaptive implementation practices. The study recommends collaborative interventions among policymakers, vendors, and industry associations to address structural disparities and to foster inclusive technological ecosystems. The research contributes both theoretically and practically to the discourse on ERP adoption, particularly within emerging markets where small industries remain foundational to economic development.